Origin and evolution of carbonaceous phyllites from Peresopolis deposit, Paraguay Belt, Mid-West Brazil - Manoel, Talitta Nunes (2017)
The Neoproterozoic Cuiabá Group of the Paraguay Belt corresponds to a thick sedimentary succession that was metamorphosed under greenschist facies metamorphic conditions during the Braziliano-Pan African Orogeny. The carbonaceous phyllites, which hosts the graphitic carbon deposit of Peresopolis, along with metadiamictites and metarenites belong to the Coxipo Formation, the upper unit of the Cuiabá Group. Light Carbon isotope signature (~-28 per mil) suggests a biogenic origin in a subaqueous reduced environment. Raman Spectroscopy is an analytical technique that shows high-resolution and high-sensitivity when applied to carbonaceous material. One hundred and sixty measurements of graphitic carbon spectrum returned a well-fit between full width at half maximum parameter (FWHM) and temperature yielding a range of 285 and 300 °C for the graphitic formation. This temperature range agrees with the temperature suggested by both the metamorphic mineral assemblage and the graphitic X-Ray diffraction patterns proving the Raman spectroscopy to be a robust geothermometer. These temperatures are in agreement with the proposed metamorphic conditions of the Internal Zone of Paraguay Belt.